2003
DOI: 10.1128/jvi.77.24.13348-13360.2003
|View full text |Cite
|
Sign up to set email alerts
|

Multispecific Vaccine-Induced Mucosal Cytotoxic TLymphocytes Reduce Acute-Phase Viral Replication but Fail inLong-Term Control of Simian Immunodeficiency VirusSIVmac239

Abstract: Given the current difficulties generating vaccine-induced neutralizing antibodies to human immunodeficiency virus (HIV),؉ controls were challenged intrarectally with SIVmac239. Massive early anamnestic cellular immune responses controlled acute-phase viral replication; however, the three vaccinees were unable to control virus replication in the chronic phase. The present study suggests that multispecific mucosal CTL, in the absence of neutralizing antibodies, can achieve a modicum of control over early viral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 58 publications
(75 reference statements)
6
70
2
Order By: Relevance
“…8); we excluded this animal from further analysis because of its uncertain infection status. We concluded, based on these results, that none of the SIV immunization regimens used results in significant protection from SIV mac239 transmission, and these findings are consistent with previous preclinical studies of CTL-based immunogens that do not contain an Env antigen (20,21).…”
Section: Resultssupporting
confidence: 78%
“…8); we excluded this animal from further analysis because of its uncertain infection status. We concluded, based on these results, that none of the SIV immunization regimens used results in significant protection from SIV mac239 transmission, and these findings are consistent with previous preclinical studies of CTL-based immunogens that do not contain an Env antigen (20,21).…”
Section: Resultssupporting
confidence: 78%
“…2A). Consistent with previous studies (26,27), the magnitude of Gag-specific responses was higher than Tat-specific throughout the follow-up period. Although it appears that the MVA-SIV vaccine vector induced slightly higher prechallenge Gag-specific responses, these differences were not significant.…”
Section: Mva-siv and Mva⌬udg-siv Induced Strong Levels Of Siv-specifisupporting
confidence: 80%
“…26). In contrast, in another study (27), a more persistent (Ͼ1 year) and robust suppression of SIV replication was observed in MamuA*01…”
Section: Discussionmentioning
confidence: 69%
“…Our finding that challenge with the highly pathogenic SHIV virus enhances cellular immunity confirms the results of a recent study (41). It has been demonstrated that HIV-specific CD8 ϩ T cell responses play an important role in controlling viral replication by cytolysis and cytokine and/or anti-virus factor production (1,2,3,42,43).…”
Section: Discussionsupporting
confidence: 81%
“…In some macaque HIV/AIDS models, SIVmac239 has been targeted as a desirable challenge virus, because it is a typical CCR5-tropic SIVmac and can cause both chronic and progressive disease in macaques (41,58,59). However, the virus is very difficult to neutralize and also very difficult to clear even from animals that have been previously immunized with homologous recombinant vector-based vaccines (41,58,59). Only live attenuated SIV has been reported to control SIVmac239 (T. Allen, Global HIV Vaccine Enterprise Meeting, Washington, October 21, 2004).…”
Section: Discussionmentioning
confidence: 99%